Assessment of Caregiver Awareness and Contribution to Curriculum Development in Kwara State - OLAYONU, Oluwanifemi Olaide; NASAMU, Rahmat Arinola; RAHEEM, Akeem Opeyemi (Ilorin Journal of Education, 2025)
Caregivers are crucial in education, shaping young learners' experiences, yet often excluded from curriculum development, limiting its relevance and effectiveness. This study investigates caregivers’ awareness and contributions to curriculum development in Kwara State. A descriptive survey design was employed focusing on all preschools across the 16 local government areas of Kwara State. The target population comprised all preschool caregivers, and a multistage sampling was used to select 132 caregivers. Systematic sampling to identify four local governments, simple random sampling to select respondents from these areas and a purposive sample for caregivers above 5 years in service. Data were collected using a self-structured questionnaire titled "Assessment of Caregiver Awareness and Contribution to Curriculum Development (ACACCD)." Expert review ensured validity, and reliability was confirmed via Cronbach's Alpha, yielding an index of 0.84. Results revealed that 75.8% of caregivers demonstrated a moderate level of awareness regarding their role in curriculum development, 18.9% had a high level, and 5.3% exhibited low awareness. In contrast, 82.6% of caregivers showed low participation in curriculum development, 17.4% exhibited moderate participation, and none demonstrated high participation. The t-test analysis indicated no significant differences in awareness or contributions based on gender, school ownership, or school location (p > 0.05). The study concludes that despite caregivers’ awareness level, their participation remains minimal, highlighting a significant gap in their involvement. Recommendations include enhancing caregiver awareness through training programs, creating inclusive participation, and ensuring equal opportunities. The study emphasises the importance of engaging caregivers in curriculum development.